2013
DOI: 10.1111/cas.12173
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of genetic lesions in rhabdomyosarcoma using a high‐density single nucleotide polymorphism array

Abstract: Rhabdomyosarcoma (RMS) is a common solid tumor in childhood divided into two histological subtypes, embryonal (ERMS) and alveolar (ARMS). The ARMS subtype shows aggressive clinical behavior with poor prognosis, while the ERMS subtype has a more favorable outcome. Because of the rarity, diagnostic diversity and heterogeneity of this tumor, its etiology remains to be completely elucidated. Thus, to identify genetic alterations associated with RMS development, we performed single nucleotide polymorphism array ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 49 publications
(84 reference statements)
4
28
0
Order By: Relevance
“…On a genetic point of view, the whole genome profiling performed in six cases reveals whole chromosome rearrangement not so different from those reported in sporadic cases: polysomy 2 and 8 are indeed the most frequent aberration in ERMS; [28,32] likewise, the 11p LOH found in 5/6 tumours in our series has been also widely encountered in sporadic ERMS. [33] Interestingly, we have observed some specific gene alterations that may synergize with the RAS pathway. The inactivation of p16 is encountered in sporadic RMS, [27,28] which emphasized that targeting the cell cycle might be of interest together with inhibiting the RAS transduction.…”
Section: Discussionmentioning
confidence: 93%
“…On a genetic point of view, the whole genome profiling performed in six cases reveals whole chromosome rearrangement not so different from those reported in sporadic cases: polysomy 2 and 8 are indeed the most frequent aberration in ERMS; [28,32] likewise, the 11p LOH found in 5/6 tumours in our series has been also widely encountered in sporadic ERMS. [33] Interestingly, we have observed some specific gene alterations that may synergize with the RAS pathway. The inactivation of p16 is encountered in sporadic RMS, [27,28] which emphasized that targeting the cell cycle might be of interest together with inhibiting the RAS transduction.…”
Section: Discussionmentioning
confidence: 93%
“…Alveolar rhabdomyosarcoma shows an aggressive phenotype, whereas embryonal has a more favorable prognosis . We previously found that ALK inhibitors were effective in select rhabdomyosarcoma cell lines with high ALK expression levels, suggesting a possible therapeutic target for ALK inhibitors in rhabdomyosarcoma . Compared with TAE684 and 2,4‐pyrimidinediamine derivative (2,4‐PDD), the different pharmacological behavior of crizotinib may be related to MET inhibition, the specific activity of crizotinib, because the rhabdomyosarcoma cell lines examined also express MET to varying degrees .…”
Section: Alk Amplification Copy Number Gain and Rare Structural Varmentioning
confidence: 99%
“…We previously found that ALK inhibitors were effective in select rhabdomyosarcoma cell lines with high ALK expression levels, suggesting a possible therapeutic target for ALK inhibitors in rhabdomyosarcoma . Compared with TAE684 and 2,4‐pyrimidinediamine derivative (2,4‐PDD), the different pharmacological behavior of crizotinib may be related to MET inhibition, the specific activity of crizotinib, because the rhabdomyosarcoma cell lines examined also express MET to varying degrees . Given that ALK amplification or copy number gain is predominantly detected in ARMS (6–17%), rhabdomyosarcoma cases with a poor prognosis may benefit from ALK inhibitors.…”
Section: Alk Amplification Copy Number Gain and Rare Structural Varmentioning
confidence: 99%
See 2 more Smart Citations